2018
DOI: 10.1111/nyas.13856
|View full text |Cite
|
Sign up to set email alerts
|

The Arctic's sea ice cover: trends, variability, predictability, and comparisons to the Antarctic

Abstract: As assessed over the period of satellite observations, October 1978 to present, there are downward linear trends in Arctic sea ice extent for all months, largest at the end of the melt season in September. The ice cover is also thinning. Downward trends in extent and thickness have been accompanied by pronounced interannual and multiyear variability, forced by both the atmosphere and ocean. As the ice thins, its response to atmospheric and oceanic forcing may be changing. In support of a busier Arctic, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 106 publications
2
135
0
1
Order By: Relevance
“…Sea ice in the region sampled by the BGEP moorings includes the southern arm of the perennial ice pack in the Beaufort Gyre as well as new ice from the Chukchi Sea recirculating in the central gyre with remnant perennial ice. Sea ice in this region has also seen some of the most rapid rates of thinning and retreat in recent years (Serreze & Meier, ; Stroeve et al, ). By tracking buoys and pseudobuoys drifting over moored IPSs, we have conclusively demonstrated that the more time that sea ice spends in the southern Beaufort Sea during summer (particularly late summer), the more melt it experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea ice in the region sampled by the BGEP moorings includes the southern arm of the perennial ice pack in the Beaufort Gyre as well as new ice from the Chukchi Sea recirculating in the central gyre with remnant perennial ice. Sea ice in this region has also seen some of the most rapid rates of thinning and retreat in recent years (Serreze & Meier, ; Stroeve et al, ). By tracking buoys and pseudobuoys drifting over moored IPSs, we have conclusively demonstrated that the more time that sea ice spends in the southern Beaufort Sea during summer (particularly late summer), the more melt it experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Serreze & Meier, 2018). Of particular significance in this regard is the loss of the oldest and thickest multiyear (MY) ice (Maslanik et al, 2011), which is expected to accelerate further ice loss (Comiso et al, 2008;Kwok, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The most striking change witnessed is the decline in Arctic sea ice extent since it has been continuously monitored by satellites beginning in the late 1970s (Parkinson & Cavalieri, ; Parkinson & DiGirolamo, ). More recently, since the early 2000s, the sea ice has experienced an increased rate of decline in extent and thickness (Serreze & Meier, ), switching to a seasonal first‐year dominated ice pack (Maslanik et al, ; Nghiem et al, ) compared to the sea ice of the 1980–1990s (e.g., Comiso et al, ; Kwok & Rothrock, ; Lindsay & Schweiger, ). This loss in sea ice coverage has allowed for the ocean surface and atmosphere to interact in regions and seasons when sea ice previously prohibited such exchanges.…”
Section: Introductionmentioning
confidence: 99%
“…The long‐term decline in the annual mean Arctic Sea Ice Extent (SIE) is one of the clearest indicators of climate change, and certainly one that generates more scientific and social concern than most (IPCC, ). Arctic SIE has decreased substantially over the last four decades, with the reduction in late summer and early autumn since the beginning of the 2000s being particularly noteworthy (e.g., Lee et al, ; Serreze & Meier, ). The environmental implications of the retreat of the Arctic ice are of great importance, and the scientific study of its causes and consequences encompasses a very broad spectrum of disciplines, including atmospheric and oceanic sciences, ecology, marine biology, and even economics and energy resources (IPCC, or Bhatt et al, for a review).…”
Section: Introductionmentioning
confidence: 99%